Clima institucional y desempeño docente en el nivel primario de la Institución Educativa Sagrado Corazón, Iquitos 2023 - Zelada Palestini, Claudia Xiomara (2024)
The aim of this study was to determine the relationship between institutional climate and the teacher performance levels of the teacher at the primary level of the educational institution Sagrado Corazón”, of Iquitos, 2023. Materials and methods: It was applied two questionnaires to 45 teachers, previous validation for experts. The study was descriptive – relational and the design was not experimental. To determine the relationship it used the non-parametric statistical test Rho of Spearman. It was observed: that resulted of the test Rho = 0,488, with a significance value p=0,001 < 0,05. Conclusion: there is a positive and significative relationship between institutional climate and the teacher performance levels of the teacher at the primary level of the educational institution Sagrado Corazón”, of Iquitos, 2023